2009
DOI: 10.1002/jcla.20276
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of combination of heart‐type fatty acid‐binding protein and ischemia‐modified albumin in patients with acute coronary syndromes and normal troponin T values

Abstract: Recent studies have suggested that hearttype fatty acid-binding protein (H-FABP) may detect ongoing myocardial damage involved in the progression of acute coronary syndromes (ACS). This study was prospectively designed to examine whether the combination of H-FABP, a marker for ongoing myocardial damage, and ischemia-modified albumin (IMA), a marker for myocardial ischemia, would effectively diagnose patients with ACS. H-FABP values above 1.5 mg/l can be correctly measured via an ELISA and 6 mg/l is the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…44 Sensitivity and specificity of these tests were, respectively, 89.0 and 80.8% for IMA, 82.9 and 80.8% for h-FABP, and 96.3 and 80.8% for the combination of IMA and h-FABP. The authors selected 108 patients with chest pain over 1 year in an ED of a university hospital in Beijing, China.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…44 Sensitivity and specificity of these tests were, respectively, 89.0 and 80.8% for IMA, 82.9 and 80.8% for h-FABP, and 96.3 and 80.8% for the combination of IMA and h-FABP. The authors selected 108 patients with chest pain over 1 year in an ED of a university hospital in Beijing, China.…”
Section: Discussionmentioning
confidence: 91%
“…The authors selected 108 patients with chest pain over 1 year in an ED of a university hospital in Beijing, China. 44 Every patient underwent coronary angiography: 52.7% had ‡70% stenosis, and 6.5% had 50% stenosis. Eighty-two patients were classified in the ACS group.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, this condition may lead to an enhancement in the plasma level of H-FABP. Previous studies have indicated that H-FABP is not only an early and sensitive marker for detecting myocardial damage in ACS (4-8) but also high in patients with ACS whose cTnT levels were normal 12 hour after the onset of symptoms (24). It was also noted that membrane permeability increases due to severe myocardial ischemia might cause H-FABP molecules, ample in cytoplasm, to be released into plasma (24).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that both the serum H-FABP and urinary L-FABP may detect ongoing myocardial damage involved in the progression of ACS and may be potentially useful in diagnosis and prognostication in patients with ACS. 64,65 The combination of H-FABP and ischemia-modified albumin measurement on admission has been shown to be highly sensitive and specific in risk stratifying ACS patients with normal cTnT levels. 64 In patients with ACS, serum H-FABP is an independent predictor of cardiac events (cardiac death or nonfatal MI) on intermediate followup (12 months) and has a greater predictive capacity for cardiac events than cTnT.…”
Section: Fabp In Cinmentioning
confidence: 99%
“…64,65 The combination of H-FABP and ischemia-modified albumin measurement on admission has been shown to be highly sensitive and specific in risk stratifying ACS patients with normal cTnT levels. 64 In patients with ACS, serum H-FABP is an independent predictor of cardiac events (cardiac death or nonfatal MI) on intermediate followup (12 months) and has a greater predictive capacity for cardiac events than cTnT. 66,67 H-FABP may also be used as a reliable marker for the evaluation of the severity of congestive HF.…”
Section: Fabp In Cinmentioning
confidence: 99%